Using facets to inform decisions on staff development and remuneration: a case study of student rating of teaching effectiveness survey - Mat Daud, Nuraihan; Abu Kassim , Noor Lide (JAM Press, 2011)
Students’ evaluations of teaching staff can be considered high-stakes, as they are often used to determine promotion, reappointment, and merit pay to academics. Using Facets, the reliability and validity of one student rating questionnaire is analysed. A total of 13,940 respondents of the Human Science Division of International Islamic University Malaysia were involved in the study. The analysis shows that the student rating questionnaire used was valid and reliable, and it allows identification of staff for the institution’s prestigious teaching excellence awards, and those needing in-service training. It was found that there was no significant difference in terms of rank, age and gender of the staff. The study also shows that the majority of staff have problems keeping the class interested and getting students to participate in class activities. Faculty also hardly discussed common errors in assignments and tests.